KERJASAMA GURU DAN ORANG TUA DALAM PEMBINAAN IBADAH ANAK DI TK AL-MUTHMAINNAH JAMBI - Nyimas Muazzomi (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
This research described in depth about the essence, background and the process of the co-operation between teachers and parents related with the management of the child's religious duties at TK Al-Muthmainnah Jambi. This research was done through three stages, those are: pre-survey, observation and the interview, and analysis of the data, the documentation, and conclusion.  Using total sampling technique, there were 102 participants (students) in this research. They were observed while doing learning activity through playing. By interview, practice, story telling, singing, demonstrating, and experience in children life. The application of cooperation between teachers and parents at TK Al-Muthmainnah in order to train the children in doing religion duties is still not formal, still very simple, and there are not yet applied the cooperation forum in form of parenting forum.Keyword : cooperation, teachers, parents